Rabies-related knowledge, attitudes, and practices of dog owners from three barangays in Los Baños, Laguna, Philippines - Piamonte, Samuel Brando H.; de la Cruz, Christian Paul P. (2016)
Rabies continues to be a health concern in the Philippines. In 2015, only 10 municipalities and one province were added to the list of rabies-free zones in the country, making a total of 35 rabies-free areas since 2008. This study was carried out to build a community-based study on rabies in three selected barangays (villages) in Los Baños, Laguna, Philippines. Specifically, it aimed to assess the knowledge, attitudes, and practices on rabies among dog owners. Through snowball sampling, 418 dog owners from the three barangays were identified and interviewed. Descriptive measures were carried out to attain the objectives of the study. It was found out that majority of the respondents have heard about rabies. However, there was an indication of limited knowledge on rabies among the dog owners, but those with higher education had relatively better knowledge on the issue. Further, attitude scores demonstrate that across personal characteristics, dog owners had a very strong positive attitude toward rabies prevention. In terms of practices, majority of respondents practices, majority of respondents practiced regular feeding and dog grooming. Also, more than half of the respondents have vaccinated their dogs and confined their dogs at home, while only a quarter reported that their dogs were registered. The researchers highly recommend strengthening information, education, and communication campaigns of the municipality by having public fora and integrating the issue in health classes among educational institutions. Policies concerning pet confinement and registration must also be strengthened by integrating the issue in communication campaings.
Keywords: Rabies prevention; Rabies in dogs; Rabies; Rabies in animals; Rabies vaccination